Question and Answers Forum

All Questions      Topic List

Logic Questions

Previous in All Question      Next in All Question      

Previous in Logic      Next in Logic      

Question Number 198288 by Safojon last updated on 16/Oct/23

Answered by mr W last updated on 17/Oct/23

4+a=a cosh (b/(2a))  11=a sinh (b/(2a))  (4+a)^2 −11^2 =a^2   ⇒a=((105)/8)  (b/(2a))=sinh^(−1)  ((11)/a)=sinh^(−1)  ((88)/(105))  ⇒?=b=2×((105)/8)×sinh^(−1)  ((88)/(105))≈20.006 m

$$\mathrm{4}+{a}={a}\:\mathrm{cosh}\:\frac{{b}}{\mathrm{2}{a}} \\ $$$$\mathrm{11}={a}\:\mathrm{sinh}\:\frac{{b}}{\mathrm{2}{a}} \\ $$$$\left(\mathrm{4}+{a}\right)^{\mathrm{2}} −\mathrm{11}^{\mathrm{2}} ={a}^{\mathrm{2}} \\ $$$$\Rightarrow{a}=\frac{\mathrm{105}}{\mathrm{8}} \\ $$$$\frac{{b}}{\mathrm{2}{a}}=\mathrm{sinh}^{−\mathrm{1}} \:\frac{\mathrm{11}}{{a}}=\mathrm{sinh}^{−\mathrm{1}} \:\frac{\mathrm{88}}{\mathrm{105}} \\ $$$$\Rightarrow?={b}=\mathrm{2}×\frac{\mathrm{105}}{\mathrm{8}}×\mathrm{sinh}^{−\mathrm{1}} \:\frac{\mathrm{88}}{\mathrm{105}}\approx\mathrm{20}.\mathrm{006}\:{m} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com